2009
DOI: 10.1080/14653240903193806
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in hematopoietic stem cell transplantation

Abstract: Mesenchymal stromal/stem cells (MSCs) of bone marrow (BM) origin not only provide the supportive microenvironmental niche for hematopoietic stem cells (HSCs) but are also capable of differentiating into various cell types of mesenchymal origin, such as bone, fat, and cartilage. In vitro and in vivo data suggest that MSCs have low inherent immunogenicity, modulate/suppress immunological responses through interactions with immune cells, and home to damaged tissues to participate in regeneration processes through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(106 citation statements)
references
References 86 publications
1
105
0
Order By: Relevance
“…Exosomes derived from BMSCs have low inherent immunogenicity because of composition similar to that of the body's own cells. 30 The use of BMSC exosomes is therefore especially promising for exosome-based cancer therapy. There are 2 purposes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes derived from BMSCs have low inherent immunogenicity because of composition similar to that of the body's own cells. 30 The use of BMSC exosomes is therefore especially promising for exosome-based cancer therapy. There are 2 purposes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 MSCs were widely tested for tissue engineering in vitro, in animals and clinical trials. 15,16 They were recently isolated from human umbilical cord Wharton's jelly (WJ-MSCs). 17 WJ-MSCs are more primitive than those isolated from other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…9 Most recently, unique immunomodulatory properties of MSCs, such as their potential use across HLA barriers, have been an area of active investigation as such properties make them of much more value in regenerative medicine. [10][11][12][13] Although immunomodulatory properties of MSCs have been extensively studied in the context of their interactions with adaptive immune cells, such as T and B lymphocytes, 14,15 their potential interactions with innate immune cells, such as macrophages, is not as well understood. Our group has recently shown that in the presence of MSCs in vitro, human macrophages not only express a higher level of cell surface marker CD206, but also assume other characteristics of anti-inflammatory type-II macrophages.…”
mentioning
confidence: 99%